Pembayangan Mandiri pada Material Bata Ringan di Iklim Tropis - Mochamad Hilmy; Dewi Ria Indriana (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
The purpose of this study was to obtained recommendations on the use of innovative building materials from the development of existing lightweight concrete designs, to decrease the building interior temperature. The research used an engineering experimental method on lightweight concrete as material tested. A profile was attached on the outer side of lightweight concrete in order to formed a shadowed effect and expected to make the building indoor temperature go lower. The result indicated that the shadows shaped by profile attached on the outer side of lightweight concrete not fully effectively in decreasing building indoor temperature. The lightweight concrete thickness affected the velocity of solar thermal radiation impact movement that goes into the buildings interior. The formation of profiles on lightweight concrete surfaces can be decrease the room temperature in at least more than 2°C. The shading was more effective if the profile form in vertical formation. The research output was a lightweight concrete prototype that was able to contribute to decrease the building indoor temperature.